Global publication trends and research hotspots of the gut-liver axis in NAFLD: A bibliometric analysis - Yang, Shuangjie; Yu, Deshuai; Liu, Junjie; Qiao, Yanfang; Gu, Shuxiao; Yang, Ran; Chai, Xinlou; Wang, Wei (Frontiers in Endocrinology, 2023)
Background Nonalcoholic Fatty Liver Disease(NAFLD)refers to a spectrum of diseases ranging from simple liver steatosis to nonalcoholic steatohepatitis (NASH) and cirrhosis. Bidirectional cross-talk between the gut-liver axis plays an important role in the pathogenesis of NAFLD. To learn more about the gut-liver axis in NAFLD, this study aims to provide a comprehensive analysis from a bibliometric perspective. Method Literature related to the gut-liver axis in NAFLD from 1989 to 2022 was extracted from the Web of Science Core Collection. Based on Microsoft Excel, CiteSpace and Vosviewer, we conducted to analyze the number of publications, countries/regions, institutions, authors, journals, references, and keywords. Results A total of 1,891 literature since 2004 was included, with the rapid growth of the number of papers on the gut-liver axis in NAFLD annually. These publications were mainly from 66 countries and 442 institutions. Of the 638 authors analyzed, Bernd Schnabl was the one with the most publications, and Patrice D. Cani was the one with the most co-citations. International Journal of Molecular Sciences is the journal with the most articles published, and Hepatology is the journal with the most citations. The most common keywords are gut microbiota, inflammation, and insulin instance, which are current research hotspots. Short-chain fatty acid, in vitro, randomized controlled trial in clinical, and diabetes mellitus represent the research frontiers in this field and are in a stage of rapid development. Conclusion This is the first study to conduct a comprehensive bibliometric analysis of publications related to the gut-liver axis in NAFLD. This study reveals that gut microbiota, inflammation, insulin resistance, short-chain fatty acids, and randomized controlled trial will be the hotspots and new trends in the gut-liver axis in NAFLD research, which could provide researchers with key research information in this field and is helpful for further exploration of new research directions.